Elucidating the virulence genes harboured by carbapenemase- and non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae rectal isolates from patients admitted to intensive care units using whole-genome sequencing in Kuwait. Issue 7 (12th July 2022) - Al Fadhli, Amani H.; Jamal, Wafaa Y.; Rotimi, Vincent O.
Abstract : Introduction. Klebsiella pneumoniae is a Gram-negative pathogen responsible for community- and nosocomial-acquired infections. The presence of an accessory genome determines the bacterial pathogenicity and the host immune response, and thus indicates multidrug-resistant strains or more virulent groups. Little is known about the virulence genes in K. pneumoniae in Kuwait. Hypothesis/Gap Statement. The diversity of virulence genes and capsule loci in K. pneumoniae isolates warrants further genomic studies to better understand their transmission within the hospitals in Kuwait. Aim. We aimed to investigate the virulence genes harboured by K. pneumoniae isolated from rectal swabs of intensive care unit (ICU) patients in two Kuwaiti teaching hospitals. Methodology. Six isolates from patients in the ICUs of Al Razi and Mubarak hospitals, designated RZH144, RZH132 RZH108 and RZH173, and MKH381 and MKH347, respectively, were subjected to whole-genome sequencing (WGS) assays. RZH144 and RZH132 were non-carbapenemase-producing K. pneumoniae (NCKP) isolates negative for genes encoding carbapenemase production by PCR assays, and the remaining four were carbapenemase-producing K. pneumoniae (CPKP) isolates. Isolates were characterized by phenotypic, PCR and WGS methods. Susceptibility testing was performed by E test and clonality by multilocus sequence typing. Analysis of the isolates' assembled contigs was carried out using Kleborate (https://pathogen.watch ). Results. An NCPE RZH132 K. pneumoniae isolate belonged to ST231-wzi104 and harboured gene clusters encoding the biosynthesis of the siderophore aerobactin ( iuc 5) on 62-3LV. The capsular locus variants were KL51 and O locus O1v2. Another NCPKP RZH144 isolate was confirmed as ST43-wzi412 and harboured KL61 and O1v1. The four CPKP isolates harboured two virulence loci – ybt14 and iuc 5 – encoding the siderophores yersiniabactin and aerobactin, respectively. They belonged to ST231-wzi104 and harboured yersiniabactin on ICEKp5 . The sequence type of ybt was YbST145-1LV. Strain RZ108 was devoid of virulence loci. Its sequence type was ST15-wzi151 and harboured KL48 and O1V1. ST231 clonal lineage isolates shared common virulence plasmid variants. Conclusion. The CPKP ST231 had the highest virulence score and contained iuc5, which was found for the first time in ST231-CPKP isolates in Kuwait.